2022
DOI: 10.3389/fvets.2022.854503
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of miRNA and mRNA Expression in Sika Deer Testes With Age

Abstract: To elucidate the complex physiological process of testis development and spermatogenesis in Sika deer, this study evaluated the changes of miRNA and mRNA profiles in the four developmental stages of testis in the juvenile (1-year-old), adolescence (3-year-old), adult (5-year-old), and aged (10-year-old) stages. The results showed that a total of 198 mature, 66 novel miRNAs, and 23,558 differentially expressed (DE) unigenes were obtained; 14,918 (8,413 up and 6,505 down), 4,988 (2,453 up and 2,535 down), and 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 105 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…Sequencing technology has widely been used in animals to mine potential regulatory molecules. The ncRNAs in testis, which have been identified and functionally verified, suggest that they are involved in testicular development and sperm regulation ( 17 19 , 33 ). In this study, we constructed a linear RNA library and miRNA library.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequencing technology has widely been used in animals to mine potential regulatory molecules. The ncRNAs in testis, which have been identified and functionally verified, suggest that they are involved in testicular development and sperm regulation ( 17 19 , 33 ). In this study, we constructed a linear RNA library and miRNA library.…”
Section: Discussionmentioning
confidence: 99%
“…Although a large number of lncRNAs and miRNAs have been identified and demonstrated to be involved in mammalian testicular function regulation (17)(18)(19), there are few studies on the expression of ncRNAs in different cells of the testis, especially on their regulatory mechanisms. It is valuable to study which non-coding genes maintain the normal physiological function of the testis by targeting LCs and SCs.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs play an important role in gene regulation in animals. However, researchers only focused on the miRNA expression of antler, muscle and testis of Sika Deer ( 10 12 ). But the miRNA study of the single organ cannot fully understand the panorama of its regulation of Cervidae growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…It plays a crucial role in gene expression, cell development, immune regulation, tumorigenesis and other life processes ( 9 ). Currently, the research on miRNAome of Sika Deer mainly focused on the rapid growth and regeneration of antler, the growth of muscle, the testis development and spermatogenesis ( 10 12 ). It lacks the analysis of miRNA expression profiles of different organs and development stages of Sika Deer.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, alterations in miRNA expression, associated with decreased fertility in males, have been determined in sperm and seminal plasma from patients using prescription drugs and illegal substances, including verapamil [ 11 ] and heroin [ 12 ], respectively. In addition, a study by Jia et al on animal models discovered miRNAs the expression profiles of which differed in relation to the age of the animals [ 13 ], which suggested that such interrelations could also apply in humans. Generally, these studies imply that miRNA dysregulation plays a notable role in male infertility; nevertheless, the impaired miRNA regulatory functions affecting spermatogenesis, spermatozoa motility and morphology remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%